2013
DOI: 10.1682/jrrd.2012.11.0202
|View full text |Cite
|
Sign up to set email alerts
|

New method of fixation of in-bone implanted prosthesis

Abstract: This article presents results on the effectiveness of a new version of the titanium porous composite skin and bone integrated pylon (SBIP). The SBIP is designed for direct skeletal attachment of limb prostheses and was evaluated in a pre-clinical study with three rabbits. In accordance with the study protocol, a new version of the pylon (SBIP-3) was implanted into the hind leg residuum of three rabbits. The SBIP-3 has side fins that are designed to improve the bond between the bone and pylon. The fins are posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…6 ). The cross section of the pylon clearly demonstrated the ingrowth of the soft tissues into the pores of the titanium, that was similar in nature to our previous experiments with non modified pylons [22, 45, 46]. With the non modified pylons (control), following 6 months after surgery we observed the patchy fibrovascular ingrowth ( Fig.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…6 ). The cross section of the pylon clearly demonstrated the ingrowth of the soft tissues into the pores of the titanium, that was similar in nature to our previous experiments with non modified pylons [22, 45, 46]. With the non modified pylons (control), following 6 months after surgery we observed the patchy fibrovascular ingrowth ( Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Specification for all modifications of the SBIP pylons, defining the four critical parameters of particle size, pore size, porosity and volume fraction, is uniquely selected and protected by US Patent # 8257435. Durability, resistance to fatigue, safety and efficiency of the SBIP specification has been confirmed in mechanical and animal studies [19, 21, 22, 27, 35 41]. …”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Similar to SBIP‐2, the SBIP‐3 is also a composite, but includes side elements (fins) that are placed in the precut slots in the cortical bone walls …”
Section: Methodsmentioning
confidence: 99%
“…Direct skeletal attachment (DSA) of limb prostheses represents an alternative technology to traditional suspension of prostheses via various socket systems, with clear indications when the sockets cannot be properly fitted. Several preclinical and clinical studies demonstrated biomechanical efficiency of the DSA in rehabilitating patients . However, the rate of implant‐related infections is still high .…”
Section: Introductionmentioning
confidence: 99%